AN EDUCATIONAL THERAPEUTIC PROGRAM OF THE FRENCH NATIONAL HEALTH INSURANCE FUND (CNAM) FOR HYPERTENSIVE AND/OR DYSLIPIDEMIC FRENCH PATIENTS: FIRST RESULTS. (June 2018) - Vaïsse, B.; Vehier, C. Mounier; Delorme, A.; Vincent, I.
Abstract : Objective: Aim: to improve the hypertensive and/or dyslipidemic French patients' awareness in their health problems and to favor a healthier lifestyle, a better Blood Pressure (BP) and lipid control, and a better patient's compliance. Design and method: Methods: this educational program realized by the CNAM in association with the French Federation of Cardiology and the French National Committee Against Hypertension contains an educational assessment, four workshops: cardiovascular risk, physical activity and nutrition, stress and tobacco, treatment and home BP measurement, and an individual follow-up of 18 months. Results: Results: this program has been proposed to 2343 patients distributed in 16 centers, 844 (44 %) agreed to participate. Average age: 61 years, 52 % of women, 21 % workers, 65 % couple living, 60 % of the patients had one or two cardiovascular risk factors and 40 % both (hypertension and dyslipidemia). The office BP control (<140/90 mm Hg) was 31 % for men and 42 % for women. The abdominal obesity (BMI > 30) occurred in 41 % for men and 26 % for women. LDL control (<1, 3 g/l) under treatment was obtained in 52% in men and 38% in women. 12 % of the subjects are smokers, 30 % felt moderate stress. A good therapeutic observance assessed by a specific questionnaire was found in only 44 %. Conclusions: Conclusion: BP and lipid controls are insufficient in this French cohort at the beginning of the program, associated with a poor observance. These results emphasize the need to provide more systematically a specific therapeutic education program to moderate risk patients (European score risk). An evaluation of the first 1000 patients will be made in 2018 to improve data collection and to perhaps allow an extension of this national program by CNAM.